2011
DOI: 10.1152/ajpgi.00011.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone induces changes in gene expression and differentiation in immature human enterocytes

Abstract: It is known that functional maturation of the small intestine occurring during the weaning period is facilitated by glucocorticoids (such as hydrocortisone, HC), including an increased expression of digestive hydrolases. However, the molecular mechanisms are not well understood, particularly in the human gut. Here we report a microarray analysis of HC-induced changes in gene expression in H4 cells (a well-characterized human fetal small intestinal epithelial cell line). This study identified a large number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
(37 reference statements)
1
21
0
1
Order By: Relevance
“…However, studies in various endothelial and nonintestinal epithelial cell lines provided evidence for the ability of glucocorticoids to stimulate tight junction sealing in the absence of inflammatory stimuli (14,16,36,60). A recent report furthermore described upregulation of multiple tight junction proteins by corticosteroids in immature enterocytes as part of their well-known ability to promote intestinal maturation (23). The aim of our study, therefore, was to investigate whether glucocorticoids regulate barrier characteristics of the intestinal epithelium in the absence of immunological factors using an in vitro model.…”
mentioning
confidence: 99%
“…However, studies in various endothelial and nonintestinal epithelial cell lines provided evidence for the ability of glucocorticoids to stimulate tight junction sealing in the absence of inflammatory stimuli (14,16,36,60). A recent report furthermore described upregulation of multiple tight junction proteins by corticosteroids in immature enterocytes as part of their well-known ability to promote intestinal maturation (23). The aim of our study, therefore, was to investigate whether glucocorticoids regulate barrier characteristics of the intestinal epithelium in the absence of immunological factors using an in vitro model.…”
mentioning
confidence: 99%
“…The overall in vitro response of human intestinal epithelial cells to GCs was also studied using microarray analysis. This work showed that hydrocortisone differ entially regulates the expression levels of protein encoding genes and enterocyte markers involved in polarization and tight junction formation [56]. Altogether, these studies underlined that both endogenous (adrenal derived) and exogenous GCs play a role dur ing the functional maturation of the gut and the maintenance of intestinal epithelial barrier function.…”
Section: Function and Roles Of Intestinal Gcsmentioning
confidence: 67%
“…The literature further has established a role for hormones such as thyroxine, cortisol, insulin, EGF, and IGF1, often secreted into colostrum, to influence the transcription, expression, and maturation of these hydrolases (James et al, 1987;Foltzer-Jourdainne et al, 1989;Foltzer-Jourdainne and Raul, 1990;Burrin et al, 2001;Petersen et al, 2002;Lu et al, 2011). These and other studies have demonstrated that several brush border hydrolases are transiently expressed and active in the neonatal colon in addition to the intestine.…”
Section: Downloaded Frommentioning
confidence: 88%